Introduction to the Special Issue: Feminist Solidarity, Resistance, and Social Justice - Manijeh Daneshpour (Social Sciences)
This Special Issue of Social Sciences, titled “Feminist Solidarity, Resistance and Social Justice”, brings together critical perspectives and original scholarship illuminating how feminist resistance and solidarity are theorized and practiced across geopolitical, cultural, and institutional contexts [...]